2007
DOI: 10.1038/sj.npp.1301526
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Reuptake Inhibition Causes Weight Loss by Increasing Locomotor Activity and Thermogenesis

Abstract: Bupropion (BUP) is a dopamine (DA) and norepinephrine (NE) reuptake inhibitor that causes mild weight loss in obese adults. Subchronic (7 day) coadministration of selective DA and NE reuptake inhibitors also causes weight loss in mice. Because weight loss was not associated with decreased caloric intake, subchronic BUP might cause weight loss through increased energy expenditure. Acute studies demonstrate that BUP or DA + NE reuptake inhibitors cause transient hypophagia and increased locomotion; though the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…This notion is supported by the observation that stimulation of monoaminergic neurotransmission also impacts the metabolic rate by increasing energy expenditure, either directly by increasing thermogenesis through activation of peripheral b 3 adrenoceptors in brown adipose tissue, or indirectly by increasing central DA receptor-dependent motor activity. These combined effects are reported for a number of MRIs, including the dual NE/5-HT and NE/DA reuptake inhibitors, sibutramine, and buproprion, respectively (Connoley et al, 1999;Liu et al, 2004;Golozoubova et al, 2006;Billes and Cowley, 2008). Although it should be noted that no tolerance to the appetite suppressing effect of tesofensine is observed in clinical settings (Astrup et al, 2008a), one possibility that warrants further investigation is whether sustained weight loss with tesofensine may involve increased energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by the observation that stimulation of monoaminergic neurotransmission also impacts the metabolic rate by increasing energy expenditure, either directly by increasing thermogenesis through activation of peripheral b 3 adrenoceptors in brown adipose tissue, or indirectly by increasing central DA receptor-dependent motor activity. These combined effects are reported for a number of MRIs, including the dual NE/5-HT and NE/DA reuptake inhibitors, sibutramine, and buproprion, respectively (Connoley et al, 1999;Liu et al, 2004;Golozoubova et al, 2006;Billes and Cowley, 2008). Although it should be noted that no tolerance to the appetite suppressing effect of tesofensine is observed in clinical settings (Astrup et al, 2008a), one possibility that warrants further investigation is whether sustained weight loss with tesofensine may involve increased energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the temperature of iBAT as a marker of both sympathoexcitation and increased energy expenditure. We have used iBAT temperature as an index of sympathetic outflow and of thermogenesis previously in other studies (Xiao et al, 2007;Billes and Cowley, 2008). We found that DIO mice have chronically elevated temperature (⌬ 0.6°C), compared with C57BL/6J mice fed a regular diet (controls) over 24 h ( p Ͻ 0.001), during both the light period and the dark period.…”
Section: Obese Mice Are Not Resistant To Leptin Effects On Thermogenesismentioning
confidence: 95%
“…iBAT temperature and locomotor activity (LA) were measured as described previously (Billes and Cowley, 2008). Under isoflurane anesthesia E-Mitters were implanted beneath the iBAT pad between the scapulae.…”
Section: Telemetric Transponder Implantation Locomotor Activity Ibamentioning
confidence: 99%
“…Emotional effects of BP have also been observed in social interactions in mice [15] . Moreover, BP induces locomotor stimulation, although this activity is mild [16][17][18] . BP has also been found to decrease not only nicotine but also the addictive and craving effects elicited by methamphetamine in humans [19] , and by cocaine in rodents [20] , as well as morphine-induced tolerance and dependence in rodents [21] .…”
Section: Introductionmentioning
confidence: 99%